2023
DOI: 10.6018/reifop.542181
|View full text |Cite
|
Sign up to set email alerts
|

Permanent training as a predictor of success in the digital competence of Education teachers carrying out the online tutorial action

Abstract: The self-perception in digital competence of teachers has been studied in depth in recent years. However, these studies have rarely focused on the process of tutorial action and how to perform this action digitally between the tutor and the students, the teachers and the family. The main objective is to analyze the incidence of continuing education as a mandatory requirement for self-perception of teachers regarding their digital competence. For this purpose, an          ex post facto design was used with a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
1
0
3
Order By: Relevance
“…Consequently, in the face of accelerated technological advance, even more so with the overwhelming development of artificial intelligence, a mandatory field of teacher training is digital training. Recent studies have shown that teachers with technological training develop superior skills to deal with complex problems, and open the academic offer online tutorial (Ruiz-Palmero, Guillén-Gámez & Tomczyk, 2023). This type of competence is often obtained through formal and non-formal methods (Souto-Seijo et al, 2020), common characteristics today obtained by "millennial generations", in which learning is not properly developed in environments of formation of specific educational spaces.…”
Section: Each Institution Requires a Diagnosismentioning
confidence: 99%
“…Consequently, in the face of accelerated technological advance, even more so with the overwhelming development of artificial intelligence, a mandatory field of teacher training is digital training. Recent studies have shown that teachers with technological training develop superior skills to deal with complex problems, and open the academic offer online tutorial (Ruiz-Palmero, Guillén-Gámez & Tomczyk, 2023). This type of competence is often obtained through formal and non-formal methods (Souto-Seijo et al, 2020), common characteristics today obtained by "millennial generations", in which learning is not properly developed in environments of formation of specific educational spaces.…”
Section: Each Institution Requires a Diagnosismentioning
confidence: 99%
“…En este orden de ideas, los autores consideran que la toma de decisiones es una de las habilidades directivas más apreciadas en aquellos que se encargan de conducir a una organización. (Ruiz Palmero et al, 2023). El proceso de la toma de decisiones es dirigido parcialmente por las emociones, la imaginación y las memorias cristalizadas en ocasionales emergencias.…”
Section: Introductionunclassified
“…Estas etapas demuestran que la toma de decisiones puede ser conducida a través del uso de variadas vías. La superación es una de las vías más reconocidas actualmente (Weyns et al, 2021;Ruiz-Palmero et al, 2023) y ella debe estar en consonancia con las etapas del proceso de la toma de decisiones. En la investigación de Pérez Bernate.…”
Section: Introductionunclassified
“…La literatura científica ha evidenciado que los profesores que se forman permanentemente para conseguir mejorar sus habilidades digitales son capaces de utilizar las TIC de forma efectiva (Ruiz-Palmero et al, 2023), y consecuentemente, también mejorando el rendimiento académico del alumnado (Cabero-Almenara et al, 2023). Pero para conseguir tal fin, es necesario contar con instrumentos válidos y fiables que permitan evaluar el nivel de competencia digital de los miembros de la comunidad educativa (Guillén-Gámez et al, 2023), con el propósito de poner el foco en aquellos colectivos que realmente necesiten y reclamen cursos de formación en habilidades digitales (Martínez-Pérez et al, 2022).…”
Section: Introductionunclassified